PercuTwist tracheostomy in an intubated patient with tracheal stent. (June 2021) - Bove, Mary; Ferraro, Fausto; Morgillo, Floriana; Natale, Giovanni; Santini, Mario; Fiorelli, Alfonso
The optimal placement of a tracheal tube following percutaneous dilator tracheostomy is technically demanding in patients with tracheal stents. We report a successful technique of tracheostomy tube placement with PercuTwist in an intubated patient with a tracheal stent for malignant stenosis. The endotracheal tube was replaced with a laryngeal mask, a 9.0-mm tracheostomy tube was inserted into the trachea over a PercuTwist percutaneous dilator and through the tracheal stent under video-bronchoscopic vision. The PercuTwist technique kept the lumen of trachea, a laryngeal mask enabled adequate ventilation, and a video-bronchoscope guided the prompt insertion of the tracheostomy tube through the stent.